2018
DOI: 10.1016/j.bbamcr.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D non-proteolytically induces proliferation and migration in human omental microvascular endothelial cells via activation of the ERK1/2 and PI3K/AKT pathways

Abstract: Epithelial ovarian cancer (EOC) frequently metastasises to the omentum, a process that requires pro-angiogenic activation of human omental microvascular endothelial cells (HOMECs) by tumour-secreted factors. We have previously shown that ovarian cancer cells secrete a range of factors that induce pro-angiogenic responses e.g. migration, in HOMECs including the lysosomal protease cathepsin D (CathD). However, the cellular mechanism by which CathD induces these cellular responses is not understood. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 44 publications
2
50
1
Order By: Relevance
“…Depletion of CTSD gene expression by RNA interference decreases proliferative response and invasive potential in human breast cancer cell through suppressing the activation of EKR1/2 pathway [45]. Epithelial ovarian cancer(EOC)-secreted CTSD acts as an extracellular ligand and induces proliferation and migration in human omental microvascular endothelial cells (HOMECs) through activation of ERK1/2 and PI3K/AKT pathways [46]. Based on our observation, we found that PC cotreated with U0126 does not affect cell viability in A549 and H1299 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of CTSD gene expression by RNA interference decreases proliferative response and invasive potential in human breast cancer cell through suppressing the activation of EKR1/2 pathway [45]. Epithelial ovarian cancer(EOC)-secreted CTSD acts as an extracellular ligand and induces proliferation and migration in human omental microvascular endothelial cells (HOMECs) through activation of ERK1/2 and PI3K/AKT pathways [46]. Based on our observation, we found that PC cotreated with U0126 does not affect cell viability in A549 and H1299 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin D, CATD (CTSD) is an acid protease that is active in the breakdown of intracellular proteins, which has been reported to be involved in the pathogenesis of several diseases, such as breast cancer and possibly Alzheimer’s disease via non-proteolytic pathways [ 64 , 65 ]. The postulated direct correlation between CTSD and MMP-2 is an interesting observation which needs further insight.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the intimate relationships between Cathepsins and cancer stimulated the conception of (macro)molecules sensitive to the presence of Cathepsins for enhanced therapeutic effect. [71][72][73][74][75][76][77] In the following, we have covered Cathepsin-sensitive drug delivery systems for anticancer therapy, by distinguishing five different types of systems: (i) polymeric; (ii) inorganic; (iii) dendritic/comb-like; (iv) lipidic and (v) protein-based/peptidic.…”
Section: Cathepsin-sensitive Drug Delivery Systems 21 Anticancer Drumentioning
confidence: 99%